Triple shape memory polymers by 4D printing - Bodaghi, M; Damanpack, A R; Liao, W H (Smart materials and structures, 2018)
This article aims at introducing triple shape memory polymers (SMPs) by four-dimensional (4D) printing technology and shaping adaptive structures for mechanical/bio-medical devices. The main approach is based on arranging hot-cold programming of SMPs with fused decomposition modeling technology to engineer adaptive structures with triple shape memory effect (SME). Experiments are conducted to characterize elasto-plastic and hyper-elastic thermo-mechanical material properties of SMPs in low and high temperatures at large deformation regime. The feasibility of the dual and triple SMPs with self-bending features is demonstrated experimentally. It is advantageous in situations either where it is desired to perform mechanical manipulations on the 4D printed objects for specific purposes or when they experience cold programming inevitably before activation. A phenomenological 3D constitutive model is developed for quantitative understanding of dual/triple SME of SMPs fabricated by 4D printing in the large deformation range. Governing equations of equilibrium are established for adaptive structures on the basis of the nonlinear Green-Lagrange strains. They are then solved by developing a finite element approach along with an elastic-predictor plastic-corrector return map procedure accomplished by the Newton-Raphson method. The computational tool is applied to simulate dual/triple SMP structures enabled by 4D printing and explore hot-cold programming mechanisms behind material tailoring. It is shown that the 4D printed dual/triple SMPs have great potential in mechanical/bio-medical applications such as self-bending gripers/stents and self-shrinking/tightening staples.